2017
DOI: 10.1080/09205063.2017.1282772
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted cryogel membranes for mitomycin C delivery

Abstract: In this study, cryogel-based implantable molecularly imprinted drug delivery systems were designed for the delivery of antineoplastic agent. Mitomycin C imprinted poly(2-hydroxyethyl methacrylate-N-methacryloyl-l-glutamic acid) cryogel membranes were produced by free-radical bulk polymerization under partially frozen conditions. The membranes were characterized by swelling tests, Fourier transform infrared spectroscopy, scanning electron microscopy, surface area measurements and in vitro hemocompatibility test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Öncel et al also designed poly(2-hydroxyethyl methacrylate- N -methacryloyl- l -glutamic acid)-based cryogel for the delivery of mitomycin C. They carried out in vitro drug delivery studies to examine the effects of cross-linker ratio and template amount and observed that the cumulative release of mitomycin C was decreased with an increase in cross-linking agent ratio and higher template amount in cryogel structure. Cytotoxicity behavior of cryogel was investigated using mouse fibroblast cell line L929, and the results showed that L929 cell viability of cryogel was measured as 97.27 ± 3.57, which means it is not toxic [79].…”
Section: Composite Cryogels As Versatile Tools For Biomedical Applmentioning
confidence: 99%
“…Öncel et al also designed poly(2-hydroxyethyl methacrylate- N -methacryloyl- l -glutamic acid)-based cryogel for the delivery of mitomycin C. They carried out in vitro drug delivery studies to examine the effects of cross-linker ratio and template amount and observed that the cumulative release of mitomycin C was decreased with an increase in cross-linking agent ratio and higher template amount in cryogel structure. Cytotoxicity behavior of cryogel was investigated using mouse fibroblast cell line L929, and the results showed that L929 cell viability of cryogel was measured as 97.27 ± 3.57, which means it is not toxic [79].…”
Section: Composite Cryogels As Versatile Tools For Biomedical Applmentioning
confidence: 99%
“…Materials generated by this technique present high chemical resistance, thermal stability, good mechanical properties and reusability [23]. Hence, considering the advantages of MI, many scientists have been using this technique to develop various advanced materials [24][25][26], such as membranes [27,28], beads [29], particles [30,31], micro-and nano-gels [32,33] or thin films [34,35], to be utilized as separation tools [36], catalysts [37] or sensors and biosensors [38] for metal recovery [39,40], drug delivery [41] and ternary mixture separation [42]. In this context, some authors have already reported the use of MI for developing TNT-MIPs using surface imprinting of silica nanoparticles [43] and nanotubes [44] or bulk imprinting of films [16,27].…”
Section: Introductionmentioning
confidence: 99%
“…They reported 7.4 optimal pH and 37 • C temperature for controlled release of curcumin. They obtained optimum values which were very compatible with in-body usage without any extreme release factors [50]. Çetin and Denizli have prepared 5-fluorouracil (5-FU) imprinted cryogel discs using a coordination complex between metal-chelate monomer MAH and 5-FU with the assistance of Cu(II) ion [51].…”
Section: Controlled Drug Deliverymentioning
confidence: 96%